2004
DOI: 10.1063/1.1738535
|View full text |Cite
|
Sign up to set email alerts
|

Soft x-ray magnetic circular dichroism study of [Co/Pd] multilayered perpendicular magnetic films

Abstract: The electronic and spin states of [Co/Pd] multilayered perpendicular magnetization films with various seedlayers have been investigated by means of soft x-ray absorption and magnetic circular dichroism spectroscopy at the Co L2,3-edges. The expectation values of the orbital angular momentum 〈Lz〉 and the spin angular momentum 〈Sz〉 of Co atom in the [Co/Pd] multilayered film were estimated using the sum rule. It was found that the seedlayer changes macroscopic magnetic properties of the [Co/Pd] multilayered film… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 44 publications
3
13
0
Order By: Relevance
“…When the energy of incident X-rays is over 760 eV, X-rays penetrate to the [Co/Pd] layer through the carbon layer, and XAS and MCD reflect the information on a few number of magnetic layers [6]. Their lineshapes are similar to that of the film sputterdeposited at 20 1C [7,8]. The figures show that the difference in the thickness of Co (CoB) negligibly affects the spectral feature for both films, e.g.…”
Section: Methodsmentioning
confidence: 79%
See 1 more Smart Citation
“…When the energy of incident X-rays is over 760 eV, X-rays penetrate to the [Co/Pd] layer through the carbon layer, and XAS and MCD reflect the information on a few number of magnetic layers [6]. Their lineshapes are similar to that of the film sputterdeposited at 20 1C [7,8]. The figures show that the difference in the thickness of Co (CoB) negligibly affects the spectral feature for both films, e.g.…”
Section: Methodsmentioning
confidence: 79%
“…X-ray MCD, together with X-ray absorption spectra (XAS), is more useful for elucidating the microscopic magnetic properties related to the unoccupied 3d electronic state of a magnetic element in the films, because information on MCD in individual atoms with elemental and orbital selectivities is obtained. We have reported an MCD study of [Co/Pd] multilayered perpendicular magnetic films with different under-layers [8], and it has been found that the under-layer affects the macroscopic magnetic properties of the [Co/Pd] n multilayered film without affecting the electronic and spin states of the upper layers of Co. In the case of N 2 -added and B-doped [Co/Pd] n films, the microscopic properties, such as electronic and spin states of the Co 3d electron, were changed by only the sputtering process with additive N 2 gas [7].…”
Section: Introductionmentioning
confidence: 99%
“…The XAS peaks and structures ascribed to monoxides of Fe, Co and Ni were also found at other energies. Because the total electron yield method is highly sensitive to film surfaces [7], the various oxides were supposed to exist in the upper part of electroless-deposited CoNiFe SULs at least. It should be noted that neither MCD signal nor soft magnetic properties were observed for the oxides because of their antiferromagnetism.…”
Section: Resultsmentioning
confidence: 99%
“…M-H loops and two-dimensional macroscopic magnetic domain images were observed with a longitudinal Kerr magnetometer and an optical surface analyzer utilizing magnet-optic Kerr effect, respectively. XAS and MCD spectra at the Fe, Co and Ni L 2,3 edges were measured at glazing incidence, 45°, adapting a total electron yield method at the soft X-ray beamline BL23SU [7,8] at SPring-8, Japan. For saturating magnetization of the SULs, another external dc magnetic field of ca.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation